Level Capacity Building in Higher Education: Toward Global Competitiveness - Sukrisno, Heni (International Journal of Engineering and Technology, 2018)
The objective of this research is to know the increasing level of continuous capacity of Higher Education in Indonesia from every level of organization from organizational, system and individual level. Every organization and institution including Universitas Wijaya Kusuma Surabaya is building capacity to achieve the vision that has been formulated in its Renstra document. The research methodology in this paper uses a qualitative approach, with the research object of Universitas Wijaya Kusuma Surabaya as a whole, as well as other work units related to the implementation of capacity building at Universitas Wijaya Kusuma Surabaya (UWKS). While the data analysis using integrated phenomenology analysis with rubric EMI (Internal Quality Evaluation) Internal Quality Assurance System (SPMI) Higher Education. The results of the research information shows increasing organizational level, system level, and individual level. The conclusion of this research is the need for minor improvements that will make the grain capacity of the system level sufficient (inadequate, but minor improvements will make it adequate) so there must be an emphasis on quality improvement at the system level to improve the capacity in the Universitas Wijaya Kusuma Surabaya.